Long-term pulmonary function and quality of life in adults after extracorporeal membrane oxygenation for respiratory failure. (April 2019) - von Bahr, Viktor; Kalzén, Håkan; Frenckner, Björn; Hultman, Jan; Frisén, K Gunilla; Lidegran, Marika K; Diaz, Sandra; Malfertheiner, Maximilian V; Millar, Jonathan E; Dobrosavljevic, Tanja; Eksborg, Staffan; Holzgraefe, Bernhard
Background: There is a significant long-term burden on survivors after acute respiratory distress syndrome, even 5 years after discharge. This is not well investigated in patients treated with extracorporeal membrane oxygenation. The objective of this study was to describe very-long-term (⩾3 years) disability in lung function and morphology, quality of life, mood disorders, walking capacity, and return to work status in extracorporeal membrane oxygenation survivors. Methods: Single-center retrospective cohort study on long-term survivors treated with extracorporeal membrane oxygenation for respiratory failure between 1995 and 2010 at a tertiary referral center in Sweden. Eligible patients were approached, and those who consented were interviewed and investigated during a day at the hospital. Results: A total of 38 patients were investigated with a median follow-up time of 9.0 years. Quality of life was reduced in several Short form 36 (SF-36) subscales and all domains of the St George's Respiratory Questionnaire, similar to previous studies in conventionally managed acute respiratory distress syndrome survivors. A reduced diffusion capacity of carbon monoxide was seen in 47% of patients, and some degree of residual lung parenchymal pathology was seen in 82%. Parenchymal pathology correlated with reductions in quality of life and diffusion capacity. Symptoms of anxiety and depression were seen in 22% and 14%, respectively. Conclusion: A significant long-term burden remains even 3–17 years after extracorporeal membrane oxygenation treatment, similar to conventionally managed acute respiratory distress syndrome survivors. Future prospective studies are needed to elucidate risk factors for these sequelae.